2018
DOI: 10.2174/1871527317666180703102536
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Metalloproteinases Panel in Multiple Sclerosis Patients Treated with Natalizumab: A Possible Answer to Natalizumab Non- Responders

Abstract: 1. The serum level of MMP9 significantly decreased by NAT treatment and correlates with MS activity; 2. After eight months of NAT treatment, the MMPs signature and the MMP9/MMP2 ratio decreased; 3. MMP9 might be used as a biomarker in MS patients treated with NAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In 2020, the effect of natalizumab use on MMPs in a mouse model was studied and the results showed that natalizumab significantly reduced the expression of MMPs and that their tissue inhibitors (TIMPs) were upregulated [ 39 ]. Another study on natalizumab showed that this drug significantly decreases the levels of MMP-9, MMP-2, MMP-3, MMP-8, and MMP-10 when used in humans [ 40 ]. As most of the therapeutics used to treat MS target the peripheral immune response, a current approach is to target disease-promoting processes, such as the reduction of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the effect of natalizumab use on MMPs in a mouse model was studied and the results showed that natalizumab significantly reduced the expression of MMPs and that their tissue inhibitors (TIMPs) were upregulated [ 39 ]. Another study on natalizumab showed that this drug significantly decreases the levels of MMP-9, MMP-2, MMP-3, MMP-8, and MMP-10 when used in humans [ 40 ]. As most of the therapeutics used to treat MS target the peripheral immune response, a current approach is to target disease-promoting processes, such as the reduction of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…A possible response to NTZ treatment has also been explored. Balasa and coworkers reported a significant decrease in serum MMP-9 after 8 months of treatment and a good correlation between the biomarker and disease activity [155] , but this finding was not confirmed by other studies [156] . In NTZ-treated patients, decreased baseline levels of MMP-9 were found in patients who developed progressive multifocal leukoencephalopathy compared with those who did not [157] .…”
Section: Mmp-9mentioning
confidence: 82%
“…In 2020, the effect of natalizumab use on MMPs in a mouse model was studied, and the results showed that natalizumab signi cantly reduced the expression of MMPs and that their tissue inhibitors (TIMPs) were upregulated (38). Another study on natalizumab showed that this drug signi cantly decreases the levels of MMP-9, MMP-2, MMP-3, MMP-8 and MMP-10 when used in humans (39). As most of the therapeutics used to treat MS target the peripheral immune response, a current approach is to target disease-promoting processes such as the reduction of MMPs.…”
Section: Discussionmentioning
confidence: 99%